Hemispheric specialization for phonological processing - Mildner, Vesna; Rukavina, Zrinka (1996)
Ear advantage as an indicator of hemispheric specialization for phonological processing was exmined during a rhyme test by means of response time. accuracy and laterality index on right-handed female subjects.
Rhyme detection as a measure of phonological processing is equally successful and fast regardless of the stimulated ear, i.e. it is symmetrically represented. the absence of asymmetry in this study may be attributed to the subjects (females), nature of measurement (perception rather than production) and global (or incinsistent procesing strategy. Responses to rhyming pairs of words are significantly faster, but only insignificantly more accurate. There is no trade-off between accuracy and response times: faster responses are more accurate.
Projekt MZOS
ENG